3D SCANNING OF HISTORICAL MONUMENTS (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
In this article, the purposes of using terrestrial laser devices, the sequence of their use, the precautions to be taken when using them, the sequence of creating a 3D format of historical monuments and buildings with the help of a laser, and the current role of this 3D laser in our time are considered.